Book review: Duvvuri Subbarao. Who Moved My Interest Rate? Leading The Reserve Bank of India through Five Turbulent Years. (June 2018) - Arora, Nitin; Gill, Harinder Kaur
Duvvuri Subbarao. Who Moved My Interest Rate? Leading The Reserve Bank of India through Five Turbulent Years . Penguin Books India Private Limited, 2016, pp. xxv + 323, ₹699, ISBN 978-0670088928